Ecosystem approaches to human health - Nielsen N. Ole (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The promotion of human health must be embedded in the wider pursuit of ecosystem health. Interventions will be impaired if ecosystem-linked determinants of health are not taken into account. In the extreme case, if ecosystems lose their capacity for renewal, society will lose life support services. Essential features of ecosystem health are the capacity to maintain integrity and to achieve reasonable and sustainable human goals. An ecosystem approach to research and management must be transdisciplinary and assure participation of stakeholders. These requisites provide a means for science to better deal with the complexity of ecosystems, and for policy-makers and managers to establish and achieve reasonable societal goals. The ecosystem approach can determine links between human health and activities or events which disturb ecosystem state and function. Examples are: landscape disturbance in agriculture, mining, forestry, urbanization, and natural disasters. An understanding of these links can provide guidance for management interventions and policy options that promote human health. An ecosystem approach to management must be adaptive because of irreducible uncertainty in ecosystem function.